2016
DOI: 10.1016/j.onehlt.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Goat farm management and Brucella serological test among goat keepers and livestock officers, 2011–2012, Nakhon Si Thammarat Province, southern Thailand

Abstract: Brucellosis, a zoonotic disease particularly affecting goats, emerged in Thailand in 2003, resulting in both an occupational hazard for goat keepers and livestock officers, and production losses. Farm management practices have been identified as risk factors associated with Brucella sero-positivity in many studies. Our finding in this study should be considered in order to strengthen the system of biosecurity control in farm animals as one health approach. The objectives of the study were to describe the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 5 publications
3
13
2
Order By: Relevance
“…This was a similar finding in animal that the seroprevalence of animal coxiellosis and brucellosis in Thailand were low as reported by previous studies (3.9% and 1.5%, respectively) [25,44]. In contrast, previous studies conducted among people having a livestock-related occupation in Thailand found that the seroprevalences of coxiellosis and brucellosis were 42.8% and 8.8%, respectively [44,45]. This may be due to the fact that the women participating in our study were not in animal-related occupations conferring a higher risk for the studied diseases.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was a similar finding in animal that the seroprevalence of animal coxiellosis and brucellosis in Thailand were low as reported by previous studies (3.9% and 1.5%, respectively) [25,44]. In contrast, previous studies conducted among people having a livestock-related occupation in Thailand found that the seroprevalences of coxiellosis and brucellosis were 42.8% and 8.8%, respectively [44,45]. This may be due to the fact that the women participating in our study were not in animal-related occupations conferring a higher risk for the studied diseases.…”
Section: Discussionsupporting
confidence: 91%
“…Very low seroprevalences of coxiellosis and brucellosis among pregnant women were found in our study (1.9% and 1.0%, respectively). This was a similar finding in animal that the seroprevalence of animal coxiellosis and brucellosis in Thailand were low as reported by previous studies (3.9% and 1.5%, respectively) [25,44]. In contrast, previous studies conducted among people having a livestock-related occupation in Thailand found that the seroprevalences of coxiellosis and brucellosis were 42.8% and 8.8%, respectively [44,45].…”
Section: Discussionsupporting
confidence: 86%
“…The low seroprevalence of brucellosis among pregnant women in our study was slightly lower than studies from Yemen [44] and Pakistan [20] in which the study participants were asymptomatic pregnant women. However, our finding was lower when compared with studies conducted among slaughterhouse workers in Pakistan (21.7%) and goat farmers and livestock officers in Thailand (8.3–8.8%) [45, 46].…”
Section: Discussioncontrasting
confidence: 92%
“…27,28 However, the perception levels differed according to the age and work experience of the healthcare providers. 24,25 Raw milk was considered to be more risky for pregnant women than raw meat by the healthcare providers in our study, a finding which was similar to a previous study which assumed a lack of healthcare providers' knowledge of the risk factors of disease transmission and barriers to counseling pregnant women. 29 Cues to action for risk screening, particularly education concerning risk exposure and notification of warning messages, was the most common reason given for an intention to do risk screening among the healthcare providers.…”
Section: Perceptions and Intention To Do Risk Screeningsupporting
confidence: 88%
“…[22][23][24] Previous studies have reported that pregnant women living in the vicinity of goat farms were at the same risk as the goat farmers of contracting zoonotic infections from a contaminated environment, particularly those living in endemic areas of those diseases. 6,25 The high level of healthcare providers' intention to do risk screening for exposure to goats or raw goat products during pregnancy in our study indicated that the healthcare providers considered themselves to have a formal role in health promotion and prevention and agreed that recognizing, diagnosing and treating zoonotic diseases among people at risk was an important part of their work. 26 A previous study conducted in the United States of America showed that the healthcare providers rarely asked about a history of animal exposure when they met their patients.…”
Section: Perceptions and Intention To Do Risk Screeningmentioning
confidence: 83%